THE ROLE OF KINESIOTHERAPY IN ENHANCING SPORTS PERFORMANCE - Jacek Sobon; Benedek Florian (Annals of the “Ştefan cel Mare” University: Physical Education and Sport Section - The Science and Art of Movement, 2019)
In this study I tried to create a link between medical-sportskinesiotherapy. This link should be oriented towards maintaining the body health, guidance to achieve a harmonious aspect and a nutritional balance. Kinesiotherapy tries successfully to manage and to make this connection.